Iranian EFL Instructors’ Perspectives on Integrating Artificial Intelligence Applications into English Language Teaching and Learning - Hossein Isaee (CV Media Inti Teknologi, 2026)
Background: AI tools are increasingly recognized for their potential to enhance language acquisition, personalize instruction, and improve classroom efficiency.Aims: This study investigates the perceptions of English as a Foreign Language (EFL) instructors in Iran regarding the integration of artificial intelligence (AI) applications into teaching and learning.Methods: A quantitative research design was employed, collecting data via a structured survey from 50 EFL instructors across public and private universities in Iran.Result: Findings indicate that most instructors viewed AI applications positively, particularly for their ability to deliver tailored feedback, foster engagement, and adapt learning to students’ individual needs. AI-assisted tools, such as Duolingo and ELSA Speak, were noted as effective for improving pronunciation, grammar, and vocabulary. However, challenges such as limited technological infrastructure, potential cultural mismatches in content, and high implementation costs were also highlighted. Statistical analysis revealed significant differences in perceptions of AI benefits based on teaching experience, but no significant differences in perceived challenges.Conclusion: The study concludes by recommending increased teacher training, investment in localized AI resources, and strategies to ensure cultural relevance in AI-driven language learning.